Stego-STFAN: A Novel Neural Network for Video Steganography - Guilherme Fay Vergara; Pedro Giacomelli; André Luiz Marques Serrano; Fábio Lúcio Lopes de Mendonça; Gabriel Arquelau Pimenta Rodrigues; Guilherme Dantas Bispo; Vinícius Pereira Gonçalves; Robson de Oliveira Albuquerque; Rafael Timóteo de Sousa Júnior (Computers, 2024)
This article presents an innovative approach to video steganography called Stego-STFAN, as by using a cheap model process to use the temporal and spatial domains together, they end up presenting fine adjustments in each frame, the Stego-STFAN had a <semantics>PSNRc</semantics> metric of 27.03 and <semantics>PSNRS</semantics> of 23.09, which is close to the state-of-art. Steganography is the ability to hide a message so that third parties cannot perceive communication between them. Thus, one of the precautions in steganography is the size of the message you want to hide, as the security of the message is inversely proportional to its size. Inspired by this principle, video steganography appears to expand channels further and incorporate data into a message. To improve the construction of better stego-frames and recovered secrets, we propose a new architecture for video steganography derived from the Spatial-Temporal Adaptive Filter Network (STFAN) in conjunction with the Attention mechanism, which together generates filters and maps dynamic frames to increase the efficiency and effectiveness of frame processing, exploiting the redundancy present in the temporal dimension of the video, as well as fine details such as edges, fast-moving pixels and the context of secret and cover frames and by using the DWT method as another feature extraction level, having the same characteristics as when applied to an image file.